Coronary thrombosis in a young male with COVID-19. (2020) - Shams, Abdullah; Ata, Fateen; Mushtaq, Kamran; Munir, Waqar; Yousaf, Zohaib
Highlights: COVID-19 can present with a broad clinical spectrum of cardiac manifestations. The procoagulant state in COVID-19 can independently increase the risk of coronary thrombosis in otherwise healthy patients. COVID-19 patients who develop typical chest pain should be investigated for acute myocardial infarction. Abstract: COVID-19 predominantly presents with respiratory symptoms, but other presentations are reported, including cardiac manifestations and thromboembolism. We present a healthy young gentleman with COVID-19 pneumonia, who developed acute ST-segment elevation myocardial infarction (STEMI) due to coronary thrombosis. He was managed successfully by primary percutaneous coronary intervention (PPCI).